2017
DOI: 10.1177/0897190017699138
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity, Polytherapy, and Drug Interactions in a Neurological Context: An Example of a Multidisciplinary Approach to Promote the Rational Use of Drugs

Abstract: The study demonstrated that the neurological patient, especially if elderly, has a high risk of DDI and ADRs and that many of these can be avoided by case discussion in multidisciplinary team meetings, in which the presence of a dedicated clinical pharmacist is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…( 29 ) Cardiovascular diseases have been associated with drug interactions, ( 27 , 28 ) which often require the combination of drugs in the treatment, as well as in patients with heart failure. Busa et al ( 30 ) also identified a correlation between an increased number of drugs prescribed and an increase in drug interactions. In addition, drugs that act on the cardiovascular system was the main group involved in the drug interactions identified.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…( 29 ) Cardiovascular diseases have been associated with drug interactions, ( 27 , 28 ) which often require the combination of drugs in the treatment, as well as in patients with heart failure. Busa et al ( 30 ) also identified a correlation between an increased number of drugs prescribed and an increase in drug interactions. In addition, drugs that act on the cardiovascular system was the main group involved in the drug interactions identified.…”
Section: Discussionmentioning
confidence: 96%
“…( 29 ) Doenças cardiovasculares têm sido associadas com presença de interações medicamentosas ( 27 , 28 ) que frequentemente requerem associação de medicamentos no tratamento, bem como em pacientes com insuficiência cardíaca. Busa et al ( 30 ) também identificaram correlação entre aumento do número de medicamentos prescritos e aumento da interação medicamentosas. Além disso, os medicamentos que atuam no sistema cardiovascular foram os principais grupos envolvidos nas interações medicamentosas identificadas.…”
Section: Discussionunclassified
“…From the other side, complete set of information about consequences of potential DDIs and final descicion about final outcome of therapy could be summarized in the presence of other informations derived as from medical and practical knowledge as also from medical records of patients (20,21). Neurological disorders are one of the most common reasons for treatment in hospital facilities in modern society (16). It is known that neurological disease has chronic and progressive clinical course and due these reasons patients in neurological ward needed to be treat mostly with more than one drug.…”
Section: Introductionmentioning
confidence: 99%
“…Our results shown that the most frequently prescribed drugs were anticonvulsants, anticoagulant drugs, antidepressants, antiarrhythmic medicines, NSAIL and ACE inhibitors. These different groups of drugs have ability to increase possibility of development of clinically relevant drugdrug interactions and due this reason, neurological patients are more vulnerable population regarding DDIs and require special concern in detecting potential drug-drug interactions in a timely manner and preventing additional deterioration of health in these complex patients(15)(16)(17)(18).Antidepressants have many indications and are frequently prescribed to neurological patients(22). It is not surprising that patients who are prescribed antidepressants have a higher risk of potential DDIs since the majority of antidepressant drugs are substrates for one or more of the cytochrome P-450 isozymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation